Impressive second harmonic generation response in a novel phase-matchable NLO-active MOF derived from achiral precursors. Issue 21 (9th May 2019) - Zhang, Yu-Xiao; Li, Bing-Xuan; Lin, Hua; Ma, Zuju; Wu, Xin-Tao; Zhu, Qi-Long
Abstract : Simple yet extraordinary: a novel 1D Zn-based MOF with promising nonlinear optical (NLO) response has been prepared from achiral precursors, which serves as a prototype to theoretically access insight into the origin of the NLO response. Abstract : It is highly desirable but challenging to design and synthesize novel non-centrosymmetric (NCS) metal–organic frameworks (MOFs) with excellent nonlinear optical (NLO) properties. And the origin of their NLO responses remains vague. Herein, a novel 1D Zn-based MOF with unique zigzag helical chains, [Zn(bct)(H2 O)2 ] (MOF-FJ1 ), has been prepared from achiral precursors. It crystallizes in an NCS space group P 21 21 21 (no. 19) and is found to be a remarkable NLO material with a strong second-harmonic-generation (SHG) response (3.5 × commercial KH2 PO4 (KDP)) and high laser-induced damage threshold (1.6 × commercial KDP). Moreover, theoretical calculations based on the length-gauge formalism are discussed to unveil a deepened cognition of the structure–property relationship, providing theoretical insight into the origin of the NLO response.